Artificial Intelligence Integration and Personalized Learning Outcomes among Secondary School Students Faskari Local Government Area Katsina State, Nigeria - Nuraddeen Adamu Kanon-Haki; Karima Abdulkarim; Sule Muhammad (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
This study examined the integration of Artificial Intelligence (AI) and its influence on personalized learning outcomes among secondary school students in Faskari Local Government Area, Katsina State, Nigeria. A quantitative descriptive survey design was adopted, with a sample of 353 students selected through multistage sampling. Data were collected using a validated questionnaire (AIIPLQ) with a reliability index of 0.88. Descriptive statistics and t-tests were used for analysis at a 0.05 level of significance. Findings revealed a significant extent of AI integration in teaching and learning (M = 3.26, p < .05), indicating that AI tools are actively utilized in classrooms. The study further found that AI-based personalized learning significantly improved students’ academic performance, with mean scores increasing from 72.18 to 78.42 (p < .05). However, challenges such as inadequate infrastructure, limited teacher competence, low digital literacy, and ethical concerns were found to significantly hinder effective AI utilization (overall M = 3.99, p < .05). The study concludes that while AI integration enhances personalized learning and academic outcomes, its effectiveness depends on addressing contextual and systemic barriers. It recommends improved infrastructure, teacher training, digital literacy development, and clear ethical policies to maximize the benefits of AI in secondary education.